Contribuições da Psicologia Histórico-Cultural para a compreensão do sofrimento/adoecimento psíquico do adolescente: discussões necessárias no espaço escolar. - Lissa Mayara dos Santos Andrade (2022)
Adolescence is a period of human development permeated by various social demands and conflicts, which are easily identified in the school institution. In this sense, understanding that the teaching-learning process can be affected when there is some factor in the adolescent's life in disorder, the objective was in general: to analyze the productions and literature on psychological suffering/illness in adolescents and their relationship with the schooling process. As specific objectives: Discuss adolescence as a Historical-Cultural phenomenon; present the main discussions about psychological suffering/disease in adolescents and the schooling process found in the Scientific Electronic Library Online (SciELO) and Brazilian Digital Library of Theses and Dissertations databases; discuss the concept of depression as a form of psychological suffering/illness from the perspective of Historical-Cultural Psychology; and question the pathologization of sadness in the face of a capitalist society. The methodology used was bibliographic research, under the light of the historical-dialectical materialist method. Thus, the first section presents the contributions of Historical-Cultural Psychology on human development, with emphasis on the period of adolescence. In the second, we present the results of the bibliographic survey with the main discussions. This information was organized in the following axes: 1) conception and characterization of adolescence; 2) understanding depression and symptoms of depression; 3) subject-school/subject-schooldepression relationship; 4) subject and peer group relationship and depression; and, 5) proposals for confrontation. Finally, in section three we discuss the understanding of psychological suffering/illness, bringing discussions about depression from the perspective of Historical-Cultural Psychology and resuming aspects of adolescence, referring to the development of higher psychological functions, formation of concepts and communication activity with peers, linking the suffering/illness that affects the adolescent's school development. In view of this, we understand that Historical-Cultural Psychology can enable an understanding of psychic suffering in a depathologized way, since it takes into account objective and subjective issues that create obstacles for the relationship of adolescents with reality. Thus, through the results of this study, it is expected to contribute with schools, with the scientific environment and with society in the understanding of adolescents in psychological distress, since understanding beyond appearance is a way to overcome the naturalization of suffering/ mental illness, so that it is possible to create proposals with the aim of emancipating and overcoming the biologizing biases that make the subjects even more ill. This work was carried out with the support of the Fundação de Apoio ao Desenvolvimento do Ensino, Ciência e Tecnologia do Estado de Mato Grosso do Sul (FUNDECT), grant process nº 71/700.166/2020. Keywords: Adolescence; Psychic Suffering; schooling; Historical-Cultural Psychology.